PENGARUH RANGKAIAN SEL PELTIER TERHADAP KINERJA MINI REFRIGERATOR PORTABLE - Firmansyah, Gilang; KW, Robertoes Koekoeh; Ilminafik, Nasrul; listyadi S, Digdo; Sholahuddin, Imam (STATOR: Jurnal Ilmiah Teknik Mesin, 2024)
Thermoelectric Cooler (TEC) / Peltier cooler box requires DC electric current in operation, so that it can be used as a tool to store portable vaccines that are useful in areas that do not have AC electricity flow. The research method uses experimental methods by making the previous research as a reference for conducting experiments with series variations on TEC. This study uses 2 TECs with a series of series and parallel TEC circuits on polyurethane cooler boxes 5,5 L (280 x 180 x 200) mm, power supplied to series and parallel TEC circuits of 20 W, 30 W, and 40 W while taking data is carried out for 60 minutes. The purpose of the study was to determine the effect of TEC cooling on the cooler, COP value, and efficiency on the system. The cooling capability of the TEC in the cooler shows the temperature in the cooler with the variation of the TEC parallel circuit lower than the series TEC. Calculation of the COP value shows the greater power given to the TEC, the COP value will be smaller, the COP value of the parallel circuit at minute 1 - 3 minutes is smaller than the series TEC, but in the 60th minute the difference in COP value between TEC series and The parallel circuit TEC is not too large. Calculation of cooling box efficiency with vaccine loading shows the highest efficiency is a parallel circuit TEC of 25,84% with input power in a 20 W system and a cooling load of 5,17 W, while the lowest efficiency is a series circuit TEC of 13,48% with input power 40 W and cooling load of 5,39W.